In Vitro Anthelmintic Activity of Ethanol Stem Bark Extract of Albizia ferruginea (Guill. & Perr.) Benth - Miriam Tagoe; Yaw Duah Boakye; Theresah Appiah Agana; Vivian Etsiapa Boamah; Christian Agyare (Journal of Parasitology Research)
Albizia ferruginea (Guill. & Perr.) Benth bark is used in the traditional medicine as a vermifuge. This study sought to determine the anthelmintic activity of the stem bark extract of Albizia ferruginea. The powdered A. ferruginea stem bark was extracted with ethanol. Phytochemical screening was carried out on A. ferruginea ethanol extract (AFE) and then screened for its anthelmintic property against Pheretima posthuma and Haemonchus contortus using the adult motility assay. The effect of AFE and its fractions on the anthelminthic activity of mebendazole and albendazole were also determined using the adult worm (P. posthuma) motility assay. AFE showed a dose-dependent anthelmintic activity against P. posthuma and H. contortus. The least concentration of AFE (0.5 mg/mL) paralyzed and killed P. posthuma within 272.50±12.42 min and 354.50±5.06 min of exposure, respectively. AFE at the least test concentration (0.14 mg/mL) caused paralysis and induced death of H. contortus, after at 63.50±2.98 and 254.96±2.44 min of exposure, respectively. AFE extract at 0.25 and 0.125 mg/mL increased the paralytic and helminthicidal activities of albendazole. The paralytic and helminthicidal activities of mebendazole were reduced when combined with AFE (0.25 and 0.125 mg/mL). Among the three fractions obtained from AFE, the methanol fraction showed the highest anthelmintic activity. The methanol fraction at 0.5 mg/mL caused paralysis after 69.90±0.15 min and death of worm after 92.53±0.74 min of exposure. The petroleum ether and ethyl acetate fractions showed relatively low anthelmintic activity. Phytochemical screening of AFE revealed the presence of tannins, saponins, glycosides, alkaloids, and coumarins. The results from this study show that A. ferruginea possesses anthelmintic activity which gives credence to its folkloric use.